2008
DOI: 10.3171/foc/2008/25/8/e20
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative results following lumbar discectomy: comparison of minimally invasive discectomy and standard microdiscectomy

Abstract: Object Minimally invasive lumbar discectomy is a refinement of the standard open microsurgical discectomy technique. Proponents of the minimally invasive technique suggest that it improves patient outcome, shortens hospital stay, and decreases hospital costs. Despite these claims there is little support in the literature to justify the adoption of minimally invasive discectomy over standard open microsurgical discectomy. In the present study, the authors address some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 21 publications
8
68
1
5
Order By: Relevance
“…17 Unlike this German et al showed that patients who underwent minimally invasive microdiscectomies had about half the length of stay compared to patients who underwent conventional microdiscectomies (0.84 days vs. 1.43 days). 22 One main reason for this is that in rural India, many patients travel a long distance to have surgery, and many other were emergent transfers from other community hospitals. Such patients insist on staying longer before going back home.…”
Section: Discussionmentioning
confidence: 99%
“…17 Unlike this German et al showed that patients who underwent minimally invasive microdiscectomies had about half the length of stay compared to patients who underwent conventional microdiscectomies (0.84 days vs. 1.43 days). 22 One main reason for this is that in rural India, many patients travel a long distance to have surgery, and many other were emergent transfers from other community hospitals. Such patients insist on staying longer before going back home.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies consistently show similar rates of overall complications and CSF leakage. 8,13,20,22 Taken together, Level I evidence suggests similar safety profiles and rates of recurrence in tubular microdiscectomy compared with standard microdiscectomy.…”
Section: Operative Considerations and Complications Of Tubular Discecmentioning
confidence: 95%
“…26 Multiple retrospective studies and a meta-analysis support similar operating times for the tubular and standard groups. 8,10,13,20,22 Therefore, Level II data suggest that operative duration may be slightly increased with tubular techniques, but this is by no means certain, because conflicting data exist.…”
Section: Operative Considerations and Complications Of Tubular Discecmentioning
confidence: 99%
See 1 more Smart Citation
“…German и соавт. [29], оценив результаты лечения 172 больных (45 оперированны эндоскопическим мето-дом, 123 -классическим методом), не выявили статисти-чески достоверных отличий между группами по таким параметрам, как продолжительность операции и частота послеоперационной ликвореи. Отмечено уменьшение продолжительности послеоперационного пребывания в стационаре, интраоперационной кровопотери, потребно-сти в наркотических анальгетиках в послеоперационном периоде при использовании микроэндоскопической тех-ники дискэктомии.…”
Section: эффективность метода эндоскопической дискэктомииunclassified